Perancangan Performansi Quality Of Service Dengan Metode Virtual Routing Redudancy Protocol (VRRP) - Mugi Raharjo; Frengki Pernando; Ahmad Fauzi (Universitas Bina Sarana Informatika, 2019)
The need for a network is the intenet is indeed already is common at this time. Do a computerized system in each routine office as well as the occurrence of problems in computer networks in a company can make the effectiveness and flexibility in an agency or company became very disturbed. In PT. PELITA Cengkareng, Tangerang Paper needs a stable internet network is the key to a company's main activity is to do every day. For it is need for a change in the system of internet network. To support all activities in the company who need access to a computer network or the internet. A stable traffic as well as the existence of a performance bond that was always adequate internet desperately needed in an era as it is today. For that VRRP (Virtual Routing Protocol Redudancy) is the solution to increase network performance can be done by the existence of this method. The existing network of companies will have a backup connectivity to backup when there are problems at the major networks